Injectable hydrogel based on oxidized galactomannan from Delonix regia and n-succinyl chitosan reinforced by chitin nanocrystals - Monteiro, Everton Lucas de Lima (2021)
Among the scaffolds commonly used to approach tissue engineering, hydrogels have been gaining prominence in recent decades. Injectable hydrogels, or formed in situ, are defined as biomaterials in which the precursors are injected in liquid form and then solidify, that is, they gel in the administration site. The use of hydrogels for biomedical applications based on starting materials such as polysaccharides is quite attractive, considering that such materials have good compatibility with biological systems. However, polysaccharide hydrogels have problems related to low mechanical properties. An alternative to overcome this problem would be the addition of reinforcing agents along the hydrogel matrix. Therefore, in this work, we present the synthesis and characterization of injectable hydrogels based on oxidized galactomannan from Delonix regia and N-succinyl chitosan (both 3% w / v) reinforced by the addition of small amounts of chitin nanocrystals. The polysaccharide changes were confirmed by spectroscopic analysis in the infrared region. Macroscopically, the hydrogel without the nanocrystals showed a translucent aspect, whereas the reinforced hydrogels showed a slightly opaque aspect, uniform distribution of the nanocrystals without any apparent aggregation point. From the modifications made, it can be assumed that the crosslinking mechanism that led to the formation of hydrogels involved the formation of cross-links of the Schiff base type (C = N) between the aldehyde groups of the oxidized galactomannan and the remaining amino groups of the N- succinyl chitosan. The nanocrystals were physically trapped and dispersed throughout the matrix, probably by establishing hydrogen bonds with the hydroxyl groups of the adjacent chains, acting as a reinforcement to create a more resilient material. The scanning electron microscopy analysis revealed that the hydrogels have a pore structure with different diameters and shapes, which favors the gas exchange and transport of nutrients. The swelling performed in water was about 10-12 times greater than when in phosphate buffer. Although the solutions containing the nanocrystals present visibly higher viscosity, their addition did not compromise the injectability of the hydrogels as shown by the test using a 26G syringe (0.45x13mm). The gelation time of the hydrogels varied between 377 and 1157 s, which is in accordance with the criteria established in the literature. The addition of nanocrystals did not significantly improve the mechanical properties for hydrogels with 0.2 and 0.4% filler and for those hydrogels with higher amounts of nanocrystals, the opposite effect was observed. The in vitro biological tests used to evaluate the cytotoxicity of the hydrogels showed that the analyzed systems showed viability above 90% and therefore can be considered safe for a possible in vivo test. Further tests are necessary for a complete characterization of these systems, but given the results obtained, it can be inferred that the hydrogels produced have the potential to be used as biomaterials, with different applications, such as cell encapsulation or controlled drug release.